The Expected Rate of Return on Pension Funds and Asset Allocation as Predictors of Portfolio Performance. - Amir, Eli; Benartzi, Shlomo (The Accounting Review, 1998)
We examine the correlation between the expected rate of return on pension assets (ERR), as reported in the financial statements, and the com- position of the pension portfolio, measured as the percent invested in equities (% Equity). Our evidence indicates that ERR and %Equity are related, but the relation is rather weak. We also examine whether ERR and %Equity are correlated with future returns on pension assets. Only %Equity is correlated with future pension returns. Our results suggest that the FASB should consider the enforcement rather than elimination of current disclosure requirements regarding pension asset composition.